A randomised controlled trial of a program based on the theory of planned behavior to promote fruit and vegetable intake among schoolchildren: PROFRUVE study protocol - M. Arrizabalaga-López; D. Rada-Fernández de Jáuregui; M. P. Portillo; O. Martínez; I. Etaio; J. R. Mauleón; E. Echevarría; F. Gómez; V. M. Rodríguez (BMC, 2018)
Abstract Background The PROFRUVE study is a controlled intervention based on the Theory of Planned Behavior (TPB), which follows those behavioral theories that have proved to be the most effective at changing infant fruit and vegetable (FV) intake pattern. The main purpose of the study is to evaluate the effectiveness of an intervention program in increasing FV consumption in schoolchildren aged 8 to 10 and based on TPB. Methods Eligible classrooms within schools from Vitoria-Gasteiz (Basque Country, Spain) will be randomly assigned to the intervention (classrooms n = 4; children n = 86) or control (classrooms n = 4; children n = 86) group. The intervention group will receive 14 sessions of 60 min during an academic year (October to June). These sessions, designed by a multidisciplinary team, are based on TPB and are directed at modifying determinants of behavior (attitudes, subjective norms, perceived behavioral control and intention of consumption), and intake of FV itself. Both the process and the evolution of consumption and determinants of behavior will be evaluated (before, during, shortly after and a year after) using validated surveys, 7 day food records, 24 h reminders and questionnaires. Discussion This study will provide a valid and useful tool to achieve changes in the consumption of FV at school level. A negative result will be helpful in redefining new strategies in the framework of changing habits in the consumption of FV. Trial Registration This study has been retrospectively registered at ClinicalTrials.gov. Identifier: NCT03400891. Data registered: 17/01/2018.